Small narrative as a way to prevent human trafficking in East Nusa Tenggara Province-Indonesia - Yakobus Fahik; Adeodata Laniria C.B Mbiri (Institute Of computer Science (IOCS), 2026)
There is a belief that small stories or testimonies from former migrant workers can provide new insights to anyone who wants to become a migrant worker to avoid being trapped in human trafficking syndicates. Efforts to combat the modus operandi of human trafficking, namely fraud, can be avoided because there is new knowledge sourced from the real experiences of former migrant workers. Therefore, in completing this research, the main problem is how can former migrant workers avoid human trafficking syndicates? This main problem is analyzed philosophically using Lyotard's perspective. In answering the main problem, we conducted in-depth interviews with former migrant workers. After the data was collected, the data was analyzed and presented again in a narrative. The purpose of this study was to find out how former migrant workers can avoid human trafficking syndicates. The results found that there are former migrant workers who did not become victims of human trafficking because, first, they dared to surrender themselves to the police in the destination country of work. Second, migrant workers from NTT did not become victims of human trafficking because they have family in the destination country who work as foremen. Third, migrant workers from NTT were avoided because they had a good attitude. Fourth, there is a connection with the origin community at the destination. This research can contribute to efforts to raise awareness among individuals seeking to become migrant workers to avoid human trafficking syndicates.